CONTEMPORARY BRAZILIAN INDIGENOUS LITERATURE IN PUBLIC SCHOOLS WITHIN THE AMAZONIAN CONTEXT (Interdisciplinary Studies Journal, 2026)
Contemporary Brazilian Indigenous literature has increasingly asserted itself as a vital tool of resistance and identity affirmation within school environments, especially in light of the ongoing challenges surrounding the effective implementation of Law No. 11.645/2008 and the pressing need for intercultural pedagogical practices. This article presents the results of a qualitative, descriptive study conducted in three public schools in the municipality of Cruzeiro do Sul, Acre, located in the heart of the Brazilian Amazon. The research aimed to understand how Indigenous literature has been incorporated into reading practices during the early years of elementary education. The study employed semi-structured interviews, analysis of pedagogical documents, and direct observation of school spaces as its primary instruments. The data were examined through content analysis, following Bardin (2016), and yielded three main categories: teachers’ conceptions of Indigenous literature, challenges to its integration in pedagogical practice, and the gap between discourse and practice. The findings reveal a fragile appropriation of Indigenous themes, marked by conceptual misunderstandings, a lack of specific teacher training, and significant gaps in school collections. The study underscores the urgent need for teacher education initiatives and public policies that foster the genuine inclusion of Indigenous voices in school curricula, contributing to the construction of an anti-racist and intercultural education committed to Brazil’s ethnic and racial diversity.
Keywords: Indigenous Literature; Indigenous Peoples; Literary Reading; Law 11,645/2008